Analisa Analisa Kapasitas dan Kebutuhan Daya Listrik untuk Mengoptimalkan Penggunaan Energi Listrik di Gedung G4 Universitas Negeri Malang: Pengoptimalan Energi Listrik Gedung G4 Universitas Negeri Malang - Sujito, Sujito; Dwi Mardika, Ainur Rohmatika; Nugroho, Zory Satrio (Politeknik Negeri Sriwijaya, Indonesia, 2022)
In general, the lighting needed in the building is indoors and outdoors. The building lighting must be turned off when not in use to suit the needs. Therefore, the design of the lighting system in the building must be equipped with a switch on the lamp. In this study, a lighting system automation tool in the building was made to shorten the time in the process of turning on the lights, thus humans do not need to manually switch. The lighting system automation in the building is made using several components, namely Arduino nan, RTC (Real Time Clock), light sensor modules, relays, and PIR (Passive Infrared Receiver) motion sensors. After testing the tools made, the results can be seen, namely, the building lighting in the room will light up at night when there is human activity and light up during the day when there is not enough light and there is human activity. Furthermore, the lighting outside the building will only turn on at night and turn off during the day.